ANALISIS KUALITAS PELAYANAN GEREJA UNTUK MENINGKATKAN PARTISIPASI PEMUDA DALAM KEGIATAN GEREJA DENGAN METODE SERVQUAL BERBASIS WEB - Grace Angelina Kacaribu; Doli Hasibuan; Jhoni Maslan (Universitas Methodist Indonesia, 2026)
Service quality is a crucial factor in maintaining congregational participation, especially among youth. Changing trends and technological developments have led the younger generation to expect innovative, accessible, and responsive services. Services that fail to meet expectations can decrease their participation in church activities. This study was conducted in the Els Generation youth community of GPdI El-Shaddai Medan with the aim of analyzing the quality of church services using the SERVQUAL method and designing a web-based application to facilitate evaluation. Data were collected through an online questionnaire from 100 respondents, supplemented by interviews and observations. Analysis was conducted on five SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy to measure the gap between expectations and perceptions. The results showed that the four main dimensions—Tangibles (-0.10), Reliability (-0.12), Responsiveness (-0.08), and Assurance (-0.07)—had a negative gap, indicating that church services have not fully met youth expectations. Only the Empathy dimension (+0.05) had a positive gap, indicating the church's strength in personal care and attention. The dimension with the largest negative gap was Reliability (-0.12), indicating a need for improvement in aspects of service reliability, such as activity consistency and schedule certainty. The developed web-based application facilitated data collection, gap calculations, and the presentation of analysis results automatically and efficiently.